Urgensi Pembentukan Lembaga Adat Urang Lom Guna Memberikan Perlindungan Suku Lom - Wirazilmustaan Wirazilmustaan; Rahmat Robuwan; Rio Armanda Agustian (PROGRESIF: Jurnal Hukum, 2020)
Bangka Belitung Province have a community called a native population known as the Lom or Urang Lom. Legal recognition of the Urang Lom community in the formation of the Village Customary Institution where Urang Lom still lives is a very important part of the perspective of legal protection. The form of legal protection against the existence of Urang Lom is only limited to the recognition of a traditional institution called Mapur Customary Institution which is under the auspices of the Malay Customary Institution of Bangka. The formal and material legality problem in the formation of the Urang Lom Customary Institution in Gunung Muda and Gunung Pelawan Villages is related to the synergy of the Mapur Customary Institution that has been formed with the Village Customary Institutions based on the Village Law. Gunung Muda Village, and Gunung Pelawan Village made the formation of the Village Customary Institution be difficult because it clashed with the village territorial area.